UPAYA MENINGKATKAN KEMAMPUAN MENULIS PUISI MELALUI TEKNIK PEMODELAN EFEKTIF DAN DAPAT MENINGKATKAN PARA GURU DAN SISWA KELAS XII SMK NEGERI 3 METRO SEMESTER GANJIL TAHUN PELAJARAN 2010/2011 - Romli, Romli (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
The observation and field notes on the process found that teachers lack guiding when students recognize and choose poetry to serve as a model. Teachers allow students to work on their own without direction and guidance. While there are some students who are not responsive, even tend to disregard the instructions and activities of the group. In general, they cleave to the work of a friend in the group. They do a lot of sideline activities that are not directly related to the teaching activities. For example, they talked about other things outside activities related to the manufacture of poetry. Meanwhile, when students do activities drafted more poetry teacher sitting at the teacherâs desk, students are left to work alone with a variety of problems and difficulties. From the results of the studentsâ learning achievement in writing poetry can be quite promising results. That is, the score obtained by the student assessment is not too bad, but it also cannot be said to be good. Average value at each grade range is 55% to 68%. These results are classified in categories enough.Keywords: Teachers, direction and guidance, writing poetry